Fatigue design of steel and composite structures : Eurocode 3 - design of steel structures, part 1-9 fatigue : Eurocode 4 - design of composite steel and concrete structures /: Eurocode 3 - design of steel structures, part 1-9 fatigue : Eurocode 4 - design of composite steel and concrete structures. (2018) - Nussbaumer, Alain, 1964-; Borges, Luís; Davaine, Laurence, 1975-; ECCS - European Convention for Constructional Steelwork
No abstract available